Climatic Description of Localities of Spizella wortheni with Free Databases - Gonzalez-Uribe, Dino Ulises; Heredia-Pineda, Feliciano; Malacar-Herrera, Irasema del Rosario; González-López, Héctor Darío (Ecosistemas y Recursos Agropecuarios, 2024)
Using free databases (FDB), National Meteorological Service (NMS) and Bioclim (BIO), the climate of Spizella wortheni was described in its historical distribution (HD), n = 15 localities. The Humidity Index (HI) and Aridity Index (AI) was obtained and compared with the current distribution (CD) m = 9. The variables were Minimum Temperature (MIT oC), Average (AVT oC), Maximum (MAT oC), Precipitation (PRE) (mm), HI and AI. S. wortheni was found to nest in places of low humidity (HI = 21.56 ± 4.54) and high aridity (AI = 4.84 ± 1.15 %). The climate of the extreme HD localities to the northwest and southeast exhibited more humid (HI = 48.07 ± 6.92), less arid (AI = 2.11 ± 0.28 %) and colder conditions (10.43 ± 1.97 oC). The FDB used didn’t have significant differences (P > 0.01) for the variables studied.
Keywords: Bioclim; geographic distribution; aridity index; humidity index; Service National Meteorologic